History material for Lithuanian schools. About the first departmental school - Raulinaitis, A. (Psichologija, 1964)
This article briefly discusses historical accounts of the first departmental school in Lithuania. Herein are the works of other historians, as well as sources associated with the school.
Keywords: history of pedagogy and departmental school